Libertarian communism Marx, Engels and the political economy of freedom - Screpanti, Ernesto (Palgrave Macmillan, 2007)
This book re-exmines and brings to light the libertarian components of Marx's and Engels' political and economic thought. Central to the book is a discussion of the notion of freedom in Marx's and Engels' work. In a post-Soviet world, there is a need to revise Marxism in the search for a libertarian foundation of political economy. The book argues that the libertarian foundations were present in Marx's and Engels' work and utilizes contemporary theories of freedom to reinterpret and analyse their original work.